A Study on Perception, Awareness and Behaviour of People towards Preventive Health Check-ups - Dr. Atish Chintamani (International Journal of Advanced Science and Technology, 2020)
A deep unmet need to redefine the norms of modern living is being accomplished by having improved responsiveness towards preventive health check-ups. This study aims to understand the perception, awareness and behaviour of people towards preventive health check-ups. The study helps to scrutinize the sources of awareness, factors influencing the perception, preferences and financial aspects of tests and post information behaviour of people towards preventive health check-ups through an online survey. The analysis of findings highlights the awareness and augmented consciousness towards regular check-ups with some thought-provoking specifics regarding the perception towards these check-ups trailed by gauzed viewpoints of unaware respondents. The upshot of the paper is intriguingly helpful to know about the role and importance these check-ups hold in today’s lifestyle.